2019
DOI: 10.1080/23311975.2019.1568655
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between TQM and project performance: Empirical evidence from Malaysian construction industry

Abstract: Many studies have suggested the adaptation and implementation of Total Quality Management (TQM) is likely to improve an organization's performance. A considerable amount of literature has examined the relationship between TQM and other elements like business performance, organizational performance, and marketing performance in different industries. However, little is known of the influence of TQM in project performance in the context of Malaysian construction organizations. The objective of the study is to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 79 publications
(130 reference statements)
0
36
0
1
Order By: Relevance
“…This can be done through fulfilling customer needs (Demirbag, Koh et al, 2006;Demirbag, Tatoglu et al, 2006;Imran et al, 2018;Jong et al, 2019;Sinha et al, 2016). The key to surviving in a global market is to focus on service quality for customers (Cristea & Mocuta, 2018).…”
Section: Public Interest Statementmentioning
confidence: 99%
“…This can be done through fulfilling customer needs (Demirbag, Koh et al, 2006;Demirbag, Tatoglu et al, 2006;Imran et al, 2018;Jong et al, 2019;Sinha et al, 2016). The key to surviving in a global market is to focus on service quality for customers (Cristea & Mocuta, 2018).…”
Section: Public Interest Statementmentioning
confidence: 99%
“…A substantial consensus exists regarding the core practices of quality management in management literature [64,65]. QMS-Core practices focused in this study are: Process Management, Customer Focus, Quality Assurance and Control and Continuous Improvement.…”
Section: Qms-core Practicesmentioning
confidence: 99%
“…Strategic planning had five items, which also explained 11.9% of the total variance. After the performance of EFA, the analysis eliminated two items (Jong et al, 2019). Specifically, the continuous improvement and the involvement of employees' items were removed.…”
Section: Results Of Efa Descriptive Statistics Correlations and Reliabilitymentioning
confidence: 99%
“…In the above equations, 'V' represents the variables of the performance measures, 'F' represents the factors that help explain the correlation among the performance measures, and 'E' is a random error. The EFA (exploratory factor analysis) that was undertaken revealed that the factors were logical and reflected the study's intended measurements accurately (Jong et al, 2019). Then, there was the use of principal components extraction joined with varimax rotation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation